Probiotic Potential of Lactic Acid Bacteria from Yellow Bamboo Shoot Fermentation using 2.5% and 5% Brine at Room Temperature - LINDAYANI LINDAYANI; LAKSMI HARTAJANIE; MONIKA PALUPI MURNIATI (Microbiology Indonesia, 2018)
Yellow bamboo shoot is a popular food material especially in Semarang because it is used as filling for lumpia (authentic food of Semarang). Beside used as filling, yellow bamboo shoot commonly known by Indonesian people. Considering bamboo shoot often processed into fermented traditional food, yellow bamboo shoot also potential to be examined as source of fermented food producing lactic acid bacteria. Lactic acid bacteria still become the most beneficial microorganisms associated with gastrointestinal system and moreover for obesity diet. The aim of this research is to study the probiotic potential of lactic acid bacteria produced from yellow bamboo shoot fermentation in 2.5% and 5% brine under room temperature (30 Â°C). From isolation, 22 single colonies obtained from 2.5% brine and 27 isolates obtained from 5% brine. The morphology and physiology analysis resulted in Lactobacillus and Streptococcus genus. All isolates were tested subsequently for probiotic potential. Based on the result, more than 50% identified isolates have probiotic potential.